Pewne Twierdzenie z Zakresu Kształtowania Wytrzymałościowego Belek Sprężonych - Brandt, A. (Engineering Transactions, 1963)
The object of the considerations are simply supported prestressed concrete beams of which form has been determined from the condition of minimum elastic potential with constant material volume. For such beams the following theorem is formulated and proved. Among all the functions determining the form of the beam the function determining the location of the prestressing force is the only depending on the weight of the beam.